A case–control study of infections caused by Klebsiella pneumoniae producing New Delhi metallo-beta-lactamase-1: Predictors and outcomes - Rodríguez-Noriega, Eduardo; Garza-González, Elvira; Bocanegra-Ibarias, Paola; Paz-Velarde, Beatriz Alejandra; Esparza-Ahumada, Sergio; González-Díaz, Esteban; Pérez-Gómez, Héctor R.; Escobedo-Sánchez, Rodrigo; León-Garnica, Gerardo; Morfín-Otero, Rayo (Frontiers in Cellular and Infection Microbiology, 2022)
Infections caused by antimicrobial-resistant bacteria are a significant cause of death worldwide, and carbapenemase-producing bacteria are the principal agents. New Delhi metallo-beta-lactamase-1 producing Klebsiella pneumoniae (KP-NDM-1) is an extensively drug-resistant bacterium that has been previously reported in Mexico. Our aim was to conduct a case–control study to describe the risk factors associated with nosocomial infections caused by K. pneumoniae producing NDM-1 in a tertiary-care hospital in Mexico. Methods: A retrospective case–-control study with patients hospitalized from January 2012 to February 2018 at the Hospital Civil de Guadalajara "Fray Antonio Alcalde" was designed. During this period, 139 patients with a culture that was positive for K. pneumoniae NDM-1 (cases) and 486 patients hospitalized in the same department and in the same date as the cases (controls) were included. Data were analyzed using SPSS v. 24, and logistic regression analysis was conducted to calculate risk factors for KP-NDM-1 infection. Results: One hundred thirty-nine case patients with a KP-NDM-1 isolate and four hundred and eighty-six control patients were analyzed. In the case group acute renal failure was a significant comorbidity, hospitalization days were extended, and significantly more deaths occurred. In a multivariate analysis of risk factors, the independent variables included the previous use of antibiotics (odds ratio, OR = 12.252), the use of a urinary catheter (OR = 5.985), a central venous catheter (OR = 5.518), and mechanical ventilation (OR 3.459) and the length of intensive care unit (ICU) stay (OR 2.334) as predictors of infection with NDM-1 K. pneumoniae. Conclusion: In this study, the previous use of antibiotics, the use of a urinary catheter, central venous catheter, and mechanical ventilation, and ICU stay were shown to be predictors of infection with NDM-1 K. pneumoniae and were independent risk factors for infection with NDM-1 K. pneumoniae